Historic wrecks as Salvable Maritime Property - Mahmud Zuhdi Mohd Nor (Fakulti Undang - Undang, 2010)
The legal position regarding salvage of historic wreck, being a major form of Malaysia’s underwater cultural heritage, can be examined from the perspective of Merchant Shipping laws. However, the need for cultural and historical preservation is an obvious competing interest that must be considered. Hence the question whether the law could effectively deal with this issue. This paper examines the status of historic wreck as a salvable maritime property under Malaysian law by looking at core provisions under Merchant Shipping Ordinance 1952 and some of the universally accepted salvage law principles with particular emphasis on the requirements for a successful salvage. This paper suggests that although the Ordinance is ill-suited to deal with the specific concerns of historic wrecks in terms of preservation mechanism, certain mechanism offered are still of practical use.